Classical Kantorovich operators revisited - Acu, A.-M.; Gonska, H. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 517.5 The main object of this paper is to improve some known estimates for the classical Kantorovich operators. We obtain aquantitative Voronovskaya-type result in terms of the second moduli of continuity, which improves some previous results.In order to explain the nonmultiplicativity of the Kantorovich operators, we present a Chebyshev – Gr¨uss inequality. TwoGr¨uss –Voronovskaya theorems for Kantorovich operators are also considered.